Determination of the Main Parameters Ensuring Braking Efficiency of Two-Axle Vehicles with Different Malfunctions in the Braking System - Balayan, R․ M.; Simonyan, A. R. (ՀԱԱՀ հիմնադրամ)
The aim of the current work is to find out the effect of malfunction in the working brake system on the main parameters of the braking process and its performance, and hence, on the accuracy of the expert’s conclusion, proposing relevant principles that should guide the experimental research. The analysis of expert practice in car technical inspection testifies that the majority of questions addressed to the experts are related to the vehicle brake system and its efficiency assessment
Keywords: Agricultural Engineering